PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT TATA EPIC PRATAMA TANGERANG - Novia, Ega; Thamrin (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the influence of leadership style and work motivation on employee performance at PT Tata Epic Pratama Tangerang. The method used is quantitative. The sampling technique used saturated sampling and a sample of 62 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study simultaneously had a significant effect on employee performance with regression Y = 8.325 + 0.413 (X1) + 0.398 (X2), the correlation coefficient value was 0.771 where the value was in the interval of 0.620 to 0.799. Meanwhile, the value of the determination coefficient (R Square) was 0.594 (59.4%). Leadership style and work motivation simultaneously had a significant effect on employee performance with the regression equation Y = 8.325 + 0,413 (X1) + 0,398 (X2). The value of the determination coefficient was 59.4% while the remaining 40.6% was influenced by other factors. The hypothesis test was obtained with an F value calculated > F table or (43.228 > 2.760).